Zinc oxide/graphene nanocomposite as efficient photoelectrode in dye-sensitized solar cells: Recent advances and future outlook - Mahalingam S.; Low F.W.; Omar A.; Manap A.; Rahim N.A.; Tan C.H.; Abdullah H.; Voon C.H.; Rokhmat M.; Wibowo E.; Oon C.S. (John Wiley and Sons Ltd, 2023)
Charge transfer; Efficiency; Electrolytes; Electron transport properties; Graphene; II-VI semiconductors; Nanocomposites; Optical properties; Solar cells; Solar power generation; TiO2 nanoparticles; Titanium dioxide; Zinc oxide; Cell-be; Cell/B.E; Cell/BE; Dye- sensitized solar cells; Graphene nanocomposites; High power conversion; Photoelectrode; Photovoltaic technology; Power conversion efficiencies; Third generation photovoltaics; Dye-sensitized solar cells